Usefulness of Percutaneous Ultrasonography for Deciding the Need of Surgical Evacuation of Epidural Hematoma After Cervical Double-door Laminoplasty. Issue 1 (February 2022) - Nakaya, Yoshiharu; Hayama, Sachio; Nakano, Atsushi; Fujishiro, Takashi; Yano, Toma; Usami, Yoshitada; Mizutani, Masahiro; Neo, Masashi
Abstract : Study Design: This was a retrospective study. Objective: The objective of this study was to investigate the diagnostic utility of percutaneous ultrasonography (PUS) for postoperative epidural hematoma (EH) as a postoperative complication. Summary of Background Data: We investigated the usefulness of PUS for determining the need of surgical evacuation of postoperative EH by comparing the postoperative magnetic resonance imaging (MRI) and PUS of the spinal cord. Materials and Methods: This study included patients who underwent cervical laminoplasty using suture anchors. Regular MRI and PUS were performed 1 week postoperatively. Whenever the patients exhibited neurological deterioration, MRI and PUS were performed. The spinal cord decompression status was classified into 3 grades using MRI and PUS. The existence of spinal pulsation was determined by PUS. Results: One hundred thirty-one patients were investigated. The decompression status by MRI and PUS, and the pulsation status by PUS showed a correlation with neurological deterioration ( P <0.001). Four cases showed postoperative neurological deterioration and required revision surgery. The decompression status in these cases was classified as "poor" by both MRI and PUS, and as "no-pulsation" by PUS pulsation. The sensitivity and specificity for neurological deterioration was 100% and 95.1% in MRI decompression, 100% and 92.9% in PUS decompression, and 100% and 99.2% in PUS pulsation, respectively. Conclusions: This is the first report that the disappearance of spinal pulsation was associated with neurological deterioration. PUS was useful in determining the need of surgical evacuation for postoperative EH. PUS should be the first choice of examination in the event of postoperative neurological deterioration following a cervical laminoplasty. When the disappearance of pulsation is confirmed, an additional hematoma evacuation surgery should be considered immediately without undertaking MRI. Level of Evidence: Level III. Abstract : Supplemental Digital Content is available in the text.